2016
DOI: 10.1039/c6tb01083k
|View full text |Cite
|
Sign up to set email alerts
|

Glioma cell invasion is significantly enhanced in composite hydrogel matrices composed of chondroitin 4- and 4,6-sulfated glycosaminoglycans

Abstract: Glioblastoma multiforme (GBM) is the most aggressive form of astrocytoma accounting for a majority of primary malignant brain tumors in the United States. Chondroitin sulfate proteoglycans (CSPGs) and their glycosaminoglycan (GAG) side chains are key constituents of the brain extracellular matrix (ECM) implicated in promoting tumor invasion. However, the mechanisms by which sulfated CS-GAGs promote brain tumor invasion are currently unknown. We hypothesize that glioma cell invasion is triggered by the altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 65 publications
2
43
0
Order By: Relevance
“…Briefly, hydrogels were flash frozen in liquid nitrogen and lyophilized. We have not observed any discernible difference in structure and porosity of lyophilized snap frozen CS‐GAG hydrogels reported in this study to hydrogels frozen overnight at −80°C as reported by us previously . They were then mounted on 10 mm SEM stubs and sputter coated (Structure Probe Inc., West Chester, PA) with gold for 30 seconds and imaged under an accelerated voltage of 5 kV.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…Briefly, hydrogels were flash frozen in liquid nitrogen and lyophilized. We have not observed any discernible difference in structure and porosity of lyophilized snap frozen CS‐GAG hydrogels reported in this study to hydrogels frozen overnight at −80°C as reported by us previously . They were then mounted on 10 mm SEM stubs and sputter coated (Structure Probe Inc., West Chester, PA) with gold for 30 seconds and imaged under an accelerated voltage of 5 kV.…”
Section: Methodssupporting
confidence: 60%
“…Cells were imaged using Fluorescein isothiocyanate (FITC) and Tetramethylrhodamine (TRITC) fluorescent filters 3 hours after seeding. Viability of transduced cells was determined by quantifying the degree of fluorescence overlap of RFP and calcein using the Mander's overlap coefficient parameters in Volocity (PerkinElmer, Waltham, MA) as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34] CSs have been shown to promote U-87 MG cell invasion by upregulating the expression of the chemokine receptor CXCR4 and CSPG receptor LAR. 35 Of note, the sulfation pattern of GAGs is decisive for the proliferation and adhesion of C6 glioma cells and relates to the invasive behavior of tumor cells by degrading the extracellular matrix. 36,37 C6S may also affect tumor metastasis by remodeling the collagen network in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The sulfate groups on the chondroitin sulfate have a high affinity for positively charged anabolic growth factors and previous work has shown that the use of these gels resulted in sustained release of fibroblast growth factor-2 (FGF-2) and brain-derived neurotrophic factor (BDNF) over a period of 15 days. 41,42 Although FGF-2 and BDNF are not anabolic growth factors typically associated with PRP or with cartilage repair, the relevant growth factors in PRP are also positively charged and might interact similarly with CS-GAG hydrogels. In turn, the concept of using biocompatible negatively charged hydrogels for providing sustained release of anabolic growth factors from PRP could be applicable to augmentation of cartilage repair in the knee.…”
mentioning
confidence: 99%